2006
DOI: 10.1007/s11064-006-9057-3
|View full text |Cite
|
Sign up to set email alerts
|

Tau Isoforms Expression in Transgenic Mouse Model of Amyotrophic Lateral Sclerosis

Abstract: Tau is a protein involved in regulation of microtubule stability, axonal differentiation and transport. Alteration of retrograde transport may lead to motor neuron degeneration. Thus alternative mRNA splicing and expression of tau isoforms were studied in a transgenic mouse model harboring the human SOD1 G93A mutation. The studies were performed on cortex, hippocampus and spinal cord of 64- and 120-day-old animals (presymptomatic and symptomatic stage) and wild type controls. Exon 10 was found in all studied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 33 publications
1
10
0
3
Order By: Relevance
“…The present work is a continuation of our previous studies [10] in which we indicated changes in tau isoforms expression in frontal cortex and hippocampus, but not in the spinal cord of transgenic adult mice harboring human SOD1 with G93A amyotrophic lateral sclerosis-associated mutation, at presymptomatic and symptomatic stage of ALS (age 64 and 120 days, respectively). We confirmed the earlier results with the use of Northern blotting.…”
Section: Introductionsupporting
confidence: 69%
See 2 more Smart Citations
“…The present work is a continuation of our previous studies [10] in which we indicated changes in tau isoforms expression in frontal cortex and hippocampus, but not in the spinal cord of transgenic adult mice harboring human SOD1 with G93A amyotrophic lateral sclerosis-associated mutation, at presymptomatic and symptomatic stage of ALS (age 64 and 120 days, respectively). We confirmed the earlier results with the use of Northern blotting.…”
Section: Introductionsupporting
confidence: 69%
“…Reverse transcription reaction, as well as the analysis of alternative splicing of exons 2, 3 (N-terminal part of tau protein) and 10 (C-terminal part) were performed as described earlier [10]. The expression of tau-mRNA isoforms was determined semi-quantitatively and expressed as the ratio of optical density band of tau isoform to optical density of 40 S ribosomal S12 protein RNA (housekeeping gene) as described earlier [10].…”
Section: Rt-pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…The N-terminal part of tau is also crucial for the determination of spacing between microtubules [33,34]. As we have shown, the N-terminal but not the C-terminal part of tau is affected in the SOD1G93A mice [28,35]. LaPointe et al [36] indicated that the first 18 amino acids at the N terminus of squid axoplasm tau are required to elicit the inhibitory effect of tau filaments on kinesin-dependent fast axonal anterograde transport.…”
Section: Discussionmentioning
confidence: 99%
“…Details of this relative quantification can be found at http://docs.appliedbiosystems.com/pebiodocs/04303859.pdf. All quantifications were normalized to an established internal control for rodent brain (ribosomal S12 protein RNA, housekeeping gene), which was coamplified as described previously by others (Heinrich et al, 2006;Usarek et al, 2006;Nanda et al, 2008). For each group the results were given as mean 6 SEM.…”
Section: Real-time Quantitative Rt-pcrmentioning
confidence: 99%